Elucidating dual-defect mechanism in rhenium disulfide nanosheets with multi-dimensional ion transport channels for ultrafast sodium storage. (November 2020) - Zong, Wei; Yang, Chao; Mo, Lulu; Ouyang, Yue; Guo, Hele; Ge, Lingfeng; Miao, Yue-E.; Rao, Dewei; Zhang, Jiangwei; Lai, Feili; Liu, Tianxi
Abstract: The sodium-ion storage property in two-dimensional transition metal dichalcogenides (TMDs) is still seriously confined due to the lacking of efficient pathways for Na + insertion, which enlightens the construction of multi-dimensional ion channels a necessary. Herein, we prepared interlayer defect, sulfur vacancy-contained ReS2 nanosheets on porous nitrogen-doped carbonized bacterial cellulose (dr-ReS2-x /NCBC). In such dual-defect configuration, the interlayer defects provide interconnected in-plane/interlamination channels for offering extra pathways of Na + insertion/extraction and shortening ionic diffusion distance, while the sulfur vacancy could further enhance the electronic conductivity and induce more active sites for Na + storage. Therefore, the dr-ReS2-x /NCBC anode displays an enhanced rate capacity (231.2 mAh g −1 at 5 A g −1 ) and a good cycling stability (187.3 mAh g −1 at 5 A g −1 after 500 cycles). Furtherly revealed by density functional theory calculations, the sodium-ion storage property is attributed to its negatively shifted binding energy for sodium ions (from −0.771 to −1.791/-1.244 eV), and alleviated structural change (from 5.8% to 3.4%/-1.6%) during sodiation/desodiation processes. The dr-ReS2-x /NCBC anode was also assembled coupling with Na3 V2 (PO4 )3 cathode as a sodium-ion full cell for practical applications. This work is expected to offer an in-depth understanding between dual-defect engineering in TMDs-based anodes and as-enhanced sodium-storage performance. Graphical abstract: The interlayer defects provide interconnected channels for offering extra pathways of Na + insertion/extraction and shortening ionic diffusion distance, while the sulfur vacancies could further enhance the electronic conductivity and induce more active sites for Na + storage. This work is expected to offer an in-depth understanding between dual-defect engineering in TMDs-based anodes and as-enhanced sodium-storage performance. Image 1 Highlights: Interlayer defect provides interconnected in-plane/interlamination channels for offering extra pathways of Na + . Sulfur vacancy effectively regulates Na + binding energy and alleviates structural change. The dr-ReS2-x /NCBC anode endows rate capability and superior cycling performance for half/full sodium storage.